Traumatic brain and spinal cord injury : challenges and developments - Morganti-Kossmann, Cristina, 1960-; Raghupathi, Ramesh; Maas, Andrew I. R. (Cambridge medicine (Series), 2012)
This book covers the medical and pathological issues related to neurotrauma and its often devastating consequences. This volume is divided into two sections, one covering the brain, the other the spinal cord. Each section discusses the following topics: The demographic in the developed and developing world where neurotrauma is witnessing a massive expansion. Major clinical issues including advanced semi-experimental monitoring techniques utilized by neurosurgeons and intensivists and the potential use of identifying markers of tissue injury. Overview of major pathophysiological changes. The development of animal models; successes and limitations. Past, current and future therapeutic strategies including rehabilitative opportunities. Presenting the most up-to-date clinical and experimental research in neurotrauma, this volume is essential reading for neurologists, neurosurgeons, intensive care physicians and rehabilitative physicians.